Biomaterial-Supported Tissue Reconstruction or Regeneration 2019
DOI: 10.5772/intechopen.85091
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Nanostructured Hydroxyapatite via Controlled Hydrothermal Route

Abstract: Hydroxyapatite represents the natural inorganic component of the bone and may be considered an essential element required for the development of bone substitutes in the field of regenerative medicine. Hydroxyapatite bone substitutes own biomimetic, osteoconductive, and osteoinductive properties thanks to their chemical-physical properties and nanostructure that play a critical role for the reconstruction of calcified tissues. Controlling the structure of hydroxyapatite nanocrystals is vital for obtaining a sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 91 publications
1
14
0
1
Order By: Relevance
“…Hu et al [59] also suggested that the effects of hydroxyapatite crystallite size should be taken into account, where the smaller nanocrystallites resulted in higher levels of ALP activity. Meanwhile, it is also well known that the solubility of hydroxyapatite is inversely related to its crystallinity [60]. Therefore, the highly crystalline HA pillars on PEO-HT4 implants, which were barely soluble in the microenvironment, could have contributed to the lower ALP activity measured.…”
Section: Cell Responsementioning
confidence: 99%
“…Hu et al [59] also suggested that the effects of hydroxyapatite crystallite size should be taken into account, where the smaller nanocrystallites resulted in higher levels of ALP activity. Meanwhile, it is also well known that the solubility of hydroxyapatite is inversely related to its crystallinity [60]. Therefore, the highly crystalline HA pillars on PEO-HT4 implants, which were barely soluble in the microenvironment, could have contributed to the lower ALP activity measured.…”
Section: Cell Responsementioning
confidence: 99%
“…In past decades, works about the synthesis of HAp by hydrothermal [10] and chemical precipitation method have been reported [11], in which the dissolution stages, crystal growth, and aging time are carried out at high temperature (above the boiling point) and pressure inside of a reactor/autoclave [12]. Nowadays, the hydrothermal method synthesis presents a greater dissolution of the precursors and more homogeneous mixtures; in addition, the pressure exerted by the equipment generates structures of smaller size and minimal porosity.…”
Section: Introductionmentioning
confidence: 99%
“…En relación con la longitud de las fibras, se aprecia un comportamiento similar con el diámetro, al tomar como referencia el pH9 (natural), se observa un incremento de 161, 199.4 y 388.8% en la longitud de las muestras en pH8, 6 y 5 respectivamente. Sin embargo para el pH7 se tiene un incremento del 118.7%, lo que demuestra que incrementa la protonación al disminuir el pH, aunque para el pH7 se tiene un aumento de la longitud, pero menor a los pH anteriores, comportamiento que se ve reflejado en el pH10, ya que presenta un crecimiento de 138.5% con respecto a las muestras de pH9 (natural), como consecuencia del uso de hidróxido de amonio al producir una mayor alcalinidad incrementa la formación de OH - (Ruffini et al, 2019). Por otra parte, el análisis por EDS confirma la presencia de Ca, P y Cl.…”
Section: Discussionunclassified